Juvenile delinquency risk factors: Individual, social, opportunity or all of these together? - Bobbio, Antonella (International journal of law, crime and justice, 2020)
There is extensive literature on risk factors leading to criminal behavior. However, most of these studies have been conducted in European and Anglo-Saxon countries, and there are few analogous studies in Latin America. Our main aim was to analyze whether the criminal risk level estimated from the interaction between antisocial motivation and criminal opportunities helps to differentiate between adolescents with and without delinquent behavior (as proposed in the Triple Risk for Delinquency Model). We measured both official and self-reported antisocial behavior in a sample of 211 young people in Argentina. The results show a significant association between delinquency and personal, social and opportunity risk factors. Also, it was possible to differentiate between adolescents with and without official and self-reported antisocial behavior with high sensitivity and specificity, based on the estimation of criminal risk levels. We discuss the relevance and implications of these findings within the particular context of this study.